DETERMINATION OF HEAVY METALS IN CHILLON RIVER SEDIMENTS BY X-RAY FLUORESCENCE - Chui B., H. (2009)
In this paper, we show the results of work in the chillón river and laboratory work, using the technique of x-ray fluorescence in the laboratories of IPEN, were analyzed more than 15 samples of chillón river sediments which have found levels of abundance of elements such as Zn, Cu, Pb, Sr, etc. It has focused the most abundant heavy metals that are of interest and may have influence on the pollution of river.